Principles of care for pregnant and parenting people with substance use disorder: the obstetrician gynecologist perspective - Barber, Cecily May; Terplan, Mishka (Frontiers in Pediatrics, 2023)
Substance use in pregnant and parenting persons is common, yet still underdiagnosed. Substance use disorder (SUD) is one of the most stigmatized and undertreated chronic medical conditions, and this is exacerbated in the perinatal period. Many providers are not sufficiently trained in screening or treatment for substance use, so gaps in care for this population persist. Punitive policies towards substance use in pregnancy have proliferated, lead to decreased prenatal care, do not improve birth outcomes, and disproportionately impact Black, Indigenous and other families of color. We discuss the importance of understanding the unique barriers of pregnancy-capable persons and drug overdose as one of the leading causes of maternal death in the United States. We highlight the principles of care from the obstetrician-gynecologist perspective including care for the dyad, person-centered language, and current medical terminology. We then review treatment of the most common substances, discuss SUD and the birthing hospitalization, and highlight the high risk of mortality in the postpartum period.